PTH-069 Nurse Telephone Triaged Straight To Test Colonoscopy. (9th June 2014) - Thapar, A; Rodney, S; Haboubi, D; Wilson, J; Bhan, C; Walshe, M; Haddow, J; Oshowo, A; Mukhtar, H
Abstract : Introduction: In 2011 patients referred with suspected colorectal cancer at our institution waited a median of 36 days (IQR28–46) for a treatment plan. This resulted in 61% of colorectal cancerstaking over 31 days to reach a decision to treat. We aimed to reduce the time spent in the diagnostic phase, which was perceived to be the main hold up in the fast track pathway. Methods: A quality improvement approach was employed to change the new pathway from the existing clinic-first service to a straight-to-test service. The new nurse-led telephone triage service confirmed symptoms and assessed fitness for colonoscopy, with higher-risk patients defaulting to flexible sigmoidoscopy or clinic. Results for the first year of the new service are presented. Results: 438 patients were referred between 1/10/2012 and 1/10/2013. 222 (50%) went straight to colonoscopy and 136 (31%) to flexible sigmoidoscopy, 46 (11%) went to clinic, 32(7%) patients did not attend and data was missing for 2(1%) patients. Final diagnoses are shown in the attached figure. Colorectal cancer was found in 14/358 patients (4%). Median time from receipt of referral to first endoscopy was 13 days (IQR 11–20), with 128/348 patients (29%) waiting more than 14 days. Median time to decision to treat colorectal cancer was 25 days (IQR 20–34) in straight to test patients, a significant reduction compared to 2010–2011 (p = 0.01), with 5/14 (36%) waiting more than 31 days. Median time to first oncological treatment was 40 days (IQR 28–44), with 1/14 (7%) waiting more than 62 days. 41/66 (62%) of patients with a normal colonoscopy were discharged directly from endoscopy back to their GP. Conclusion: The new straight to test service was applicable to the majority of new colorectal fast track patients and a high patient uptake was observed. Colorectal cancer was in fact uncommon, which is being fed back to those referring into the system. Physical colorectal clinic appointments were saved in four-fifths of new patients and in two-thirds of those with a normal colonoscopy, which could be allocated to newly diagnosed cancers, or those requiring treatment for benign conditions. The straight to endoscopy service resulted in an average reduction of 11 days in making a treatment plan for new colorectal cancers. This contributed towards a low rate of breaches of the 62 day treatment target. However one-third of new cancer patients still waited over a month for a decision to treat, highlighting the extra time required for ancillary investigations and MDT discussion. These can be addressed by triggering staging investigations and MDT discussion at the time of endoscopy. Disclosure of Interest: None Declared.